ControlTree: Navigating and Selecting in a Large Tree - Appert, Caroline; Fekete, Jean-Daniel (UIST'06: Adjunct Proceedings of the Annual ACM Symposium on User Interface Software and Technology, 2006)
We introduce ControlTree, a novel interface using crossing interaction to navigate and select nodes in a large tree. ControlTree combines an optimized dynamic layout with interaction features to quickly reach a node in a node-link tree representation.